Challenges in autoimmune polyendocrine syndrome type 2 with the full triad induced by anti-programmed cell death 1: a case report and review of the literature - Pan, Qin; Li, Ping (Frontiers in Immunology, 2024)
Background: Immune checkpoint inhibitors (ICPis) induce autoimmune diseases, including autoimmune polyendocrine syndrome type 2 (APS-2), which is defined as a combination of at least two of the following endocrinopathies: autoimmune thyroid disease, type 1 diabetes, and Addison's disease. Cases with the full triad are rare. We present a case of an elderly woman who developed APS-2 with the complete triad shortly after starting anti-programmed cell death 1 (anti-PD1) treatment and review the related literature.Case: A 60-year-old woman, without any personal or family history of autoimmune and endocrine diseases, started the immunotherapy of anti-PD1 (camrelizumab) for squamous cell carcinoma of the urethral meatus. She developed primary hypothyroidism with elevated antibodies to thyroid peroxidase and thyroglobulin after 25 weeks of treatment, and developed primary adrenal insufficiency with adrenal crisis and fulminant type 1 diabetes with ketoacidosis after 45 weeks. Therefore, this patient met the diagnosis of APS-2 and was given multiple hormone replacement including glucocorticoid, levothyroxine and insuiln therapy.Continuous improvement was achieved through regular monitoring and titration of the dosage.Conclusions: Different components of APS-2 may appear at different time points after anti-PD1 administration, and can be acute and life-threatening. A good prognosis can be obtained by appropriate replacement with multiple hormones.Insights: With the clinical application of ICPis to APS-2, the complexity of its treatment should be paid enough attention.